Synthesis, characterization, and electrochemistry of five diiron propane-1, 3-dithiolate complexes with substituted phosphine ligands. Issue 15 (3rd August 2019) - Yan, Lin; Hu, Meng-Yuan; Mu, Chao; Li, Ao; Liu, Xu-Feng; Zhao, Pei-Hua; Li, Yu-Long; Jiang, Zhong-Qing; Wu, Hong-Ke
Abstract: In this paper, five diiron propane-1, 3-dithiolate complexes containing substituted phosphine ligands were prepared and structurally characterized. Treatment of [Fe2 (CO)6 ( μ -SCH2 CH2 CH2 S)] (1 ) with a monophosphine ligand methyl diphenylphosphinite, ethyl diphenylphosphinite, 4-(dimethylamino)phenyldiphenylphosphine, tris(2-methoxyphenyl)phosphine, or tris(4-chlorophenyl)phosphine in the presence of Me3 NO·2H2 O as the decarbonylating agent gave the corresponding phosphine-substituted analogues [Fe2 (CO)5 (L)( μ -SCH2 CH2 CH2 S)] [L = Ph2 POCH3, 2 ; Ph2 POCH2 CH3, 3 ; Ph2 P(4-C6 H4 NMe2 ), 4 ; P(2-C6 H4 OCH3 )3, 5 ; P(4-C6 H4 Cl)3, 6 ] in 73–93% yields. Complexes 2 –6 have been characterized by elemental analysis, spectroscopy, and X-ray crystallography. Additionally, electrochemical studies have shown that 2 –6 can catalyze the reduction of protons to H2 in the presence of HOAc. Abstract :